OP0136 Siblings of patients with rheumatoid arthritis are at increased risk of acute coronary syndrome. (12th June 2018) - Westerlind, H.; Holmqvist, M.; Ljung, L.; Frisell, T.; Askling, J.
Abstract : Background: Patients with rheumatoid arthritis (RA) are at increased risk of cardiovascular disease such as acute coronary syndromes (ACS), which cannot entirely be explained by traditional cardiovascular risk factors. Studies have shown an association between RA disease severity and risk of ACS, speaking for a contribution of the RA disease per se to the excess ACS risk. In a recent report, however, we demonstrated that despite more efficient control of inflammation in RA during the recent years, the excess risk for ACS among patients with RA compared to the general population remains 1 . This finding suggests that besides effects related to the RA disease per se, there may be a shared susceptibility. If the excess risk of ACS in patients with RA were increased due to this, an increased risk of ACS would be observed also in individuals with a similar genetic set-up and background as the patients with RA, such as their siblings. Objectives: To investigate any potential shared susceptibility between RA and ACS by estimating the risk of ACS in full siblings of patients with (vs. without) RA. Methods: We used the Swedish Rheumatology Quality register (SRQ) to identify an early RA cohort diagnosed between 1996–2015, which was linked to the Swedish Multigeneration Register, Patient Register, the Cause of Death register, and the Total Population Register. Through this, we sampled five general population comparator subjects to each patient with RA, matched by birth year and sex, and identified all full siblings to patients with RA and for their comparator subjects born within five years of their index case. The comparators, and all siblings, were required to be alive and living in Sweden at the time of the index patient's RA diagnosis (=start of follow-up). All unique individuals were then followed for ACS (defined as first ever hospitalisation for ACS (ICD10: I21 or I20.0) or MI listed as the cause of death), and censored at death, migration, RA diagnosis (for non-RA subjects) or the end of the study (Dec 31 st 2015). We calculated hazard ratios (HR) using a Cox proportional hazards model, adjusting for age, sex and calendar period of diagnosis. Confidence intervals (CI) were estimated using a robust sandwich estimator. Results: We identified 7492 patients with RA who had 10 671 full siblings, and 35 120 population comparator subjects with 47 137 full siblings. The HR for ACS was 1.44 (95% CI: 1.25 to 1.66) and 1.23 (95% CI: 1.09 to 1.40) for patients with RA and their siblings, respectively, compared to the comparator subjects. A direct comparison between the RA patients and their RA-free siblings confirmed the familial association between RA and ACS, HR 1.19 (95% CI: 1.02 to 1.38). Conclusions: The increased risk of ACS in siblings of patients with RA a) provide evidence of shared susceptibility between RA and ACS, the nature of which needs to be further investigated, and b) suggests that to bring down the CV risk in RA to that in the general population, cardiopreventive measures must go beyond optimised RA disease control. Reference: [1] Holmqvist M, Ljung L, Askling J Acute coronary syndrome in new-onset rheumatoid arthritis: a population-based nationwide cohort study of time trends in risks and excess risks, Ann Rheum Dis2017 Disclosure of Interest: H. Westerlind: None declared, M. Holmqvist: None declared, L. Ljung: None declared, T. Frisell: None declared, J. Askling Grant/research support from: Johan Askling has or has had research agreements with Abbvie, BMS, MSD, Pfizer, Roche, Astra-Zeneca, Eli Lilly, Samsung Bioepis, and UCB, mainly in the context of safety monitoring of biologics via ARTIS. Karolinska Institutet has received remuneration for JA participating in advisory boards arranged by Pfizer and Eli Lilly.